Thirst for Information and Needs Reflections of Type 2 Diabetes Patients Receiving Insulin Treatment in North-East Ethiopia: A Qualitative Exploration - Ewunetie Mekashaw Bayked; Birhanu Demeke Workneh; Mesfin Haile Kahissay (Korean Society for Preventive Medicine, 2021)
Objectives: Ongoing, proactive, planned, and patient-centered diabetes education is the cornerstone of care for all persons with diabetes. Thus, the aim of this study was to explore the information needs of type 2 diabetes mellitus patients receiving insulin treatment in North-East Ethiopia. Methods: The study was conducted from July 2019 to January 2020 using a qualitative enquiry (phenomenological approach) with purposive sampling. Face-to-face in-depth interviews were used to collect data until reaching theoretical saturation. The participants were type 2 diabetes patients receiving insulin treatment. They were identified from the diabetes patients' registration book at the diabetes clinic and interviewed at their appointment time, and were selected to include wide variations in terms of socio-demographic characteristics. Twenty-four participants (11 men and 13 women), with a median age of 57 years, were interviewed. The data were organized using QDA Miner Lite version 2.0.7 and analyzed thematically using narrative strategies. Results: Most participants had not heard of diabetes before their diagnosis. They had limited knowledge of diabetes, but ascribed different connotations for it in the local language (Amharic). The needs reflections of patients were categorized into diabetes education and participants' recommendations. Diabetes education was totally absent at hospitals, and patients received education primarily from the Ethiopian Diabetes Association and broadcast and digital media. Thus, the major concern of patients was the availability of diabetes education programs at health institutions. Conclusions: Patients' main concern was the absence of routine diabetes education, which necessitates urgent action to implement diabetes education programs, especially at health institutions.